Rotational Mechanics

A solid cylinder of mass m m and radius r r lies flat on friction less horizontal table, with a mass less string running halfway around it, as shown in figure. An object also of mass m m is attached to one end of the string, and you pull on the other end with a force T T . The circumference of the cylinder is sufficiently rough so that the string does not slip with respect to it. What is the acceleration of the mass m attached to the end of the string?

Note : Give your answer with magnitude and direction. Choose right side to be positive and left side to be negative.

Also try my set .
2 T 3 m -\frac { 2T }{ 3m } T 4 m -\frac { T }{ 4m } \quad T 2 m -\frac { T }{ 2m } \quad 3 T 2 m -\frac { 3T }{ 2m }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Satvik Pandey
Oct 16, 2014

First we have to draw FBDs.

Figure Figure Applying newton's second law on cylinder

So ( T + F ) = m a (T+F)=ma ..........................(1)

Let the angular acceleration of pulley be α \alpha in clockwise direction. Let clockwise direction be positive

So ( T F ) r = I α (T-F)r=I\alpha

Here I = m r 2 2 I=\frac { m{ r }^{ 2 } }{ 2 }

So α = 2 ( T F ) m r \alpha=\frac{2(T-F)}{mr} ........(2)

Now we will get other equation be equating accelerations at the point of contact of cylinder and string.

Let the point 1 be on the string and point 2 be on the pulley. As the string is not slipping so acceleration of point 1 and 2 are equal.

Also acceleration of point 1 is equal to the acceleration of object.

Let a 1 a_{1} be the acceleration of the object.

So a 1 = F m a_{1}=\frac{F}{m} .........................(3)

NOTE- The acceleration of the object will be towards left.

Now point 2 has two accelerations

1) Due to translation which is equal to a a towards right

2) Due to rotation which is equal to r α r\alpha towards left.

Let us assume right side to be positive and left side to be negative.

Then a 1 = a r α -a_{1}=a-r\alpha

So F m = 2 ( T F ) m r T + F m \frac{F}{m}=\frac{2(T-F)}{mr}-\frac{T+F}{m}

So F = T 4 F=\frac{T}{4} ..............(4)

Now from eq(3)

a 1 = F m a_{1} = -\frac{F}{m}

From eq(4)

a 1 = T 4 m a_{1} = -\frac{T}{4m}

nice one i missed a sign in the last equation ! :(

Rohith M.Athreya - 5 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...